Peran Manajemen Syariah Dalam Meningkatkan Kinerja Bank Syariah Di Era Digital - Sifa', Moh Agus; Zaenal Azis Muctharom, Moch. (JPSDa: Jurnal Perbankan Syariah Darussalam, 2026)
Digital transformation has become inevitable for the banking industry, including Islamic banking. The development of digital technology presents both opportunities and challenges for Islamic banks in improving operational performance without neglecting compliance with Islamic principles. This study aims to examine the role of Islamic management in supporting the development of digital products and services and its impact on the performance of Islamic banks in the digital era. The research method used is a literature study by analyzing various scientific sources such as journals, academic articles, and official reports related to digitalization and Islamic banking. The results show that the implementation of digital technology has a positive impact on the performance of Islamic banks, particularly in improving operational cost efficiency, service quality to customers, and expanding financial inclusion. Islamic management plays a strategic role in ensuring that developed digital innovations remain in line with Islamic principles, such as the prohibition of riba (usury), gharar (gharar), and maisir (gambling). However, this study also found obstacles in the digitalization process, including regulations that are not fully adaptive to technological developments and low digital literacy among customers and human resources in Islamic banks. Therefore, this study recommends strengthening the role of sharia management in digitalization supervision, improving human resource competency, and closer collaboration between sharia banks and regulators to realize sustainable digital transformation in accordance with sharia principles.